Política cultural da comunidade surda : uma análise comparativa entre os países sul-americanos - Krause, Keli (2022)
This thesis deals with a comparative analysis between the sociocultural and political context of five South American countries (Argentina, Brazil, Paraguay, Venezuela and Uruguay), addressing the cultural policy of the deaf community and presenting comparative frameworks of human rights. To understand the situation from a social and political phenomenological perspective within the context of deaf social movements and their claims for public policies for the deaf community, the struggle for rights and citizenship. The study presents the elementary rights of the deaf community as a minority, focusing on public policy practices, within a perspective of social constructivism, with the objective of analyzing the policy for the deaf community and comparing its mobilizations in each country, thus presenting its social structure of history and its culture in political processes, and also a broader sense of deaf rights in the legal field. Thus, this thesis makes a brief comparison on the guarantee of human rights through public policies, contextualized in the various areas of life of the deaf community, with quality and accessible to all, and seeking to understand and discuss citizenship in the exercise of power policy regarding accessibility.